2012
DOI: 10.1007/s10933-012-9579-4
|View full text |Cite
|
Sign up to set email alerts
|

Phantom midge-based models for inferring past fish abundances

Abstract: We sampled living and subfossil phantom midge (Diptera: Chaoboridae) larvae from surface sediments of 21 small lakes in Southern Sweden to examine the influence of fish and selected abiotic variables on the abundance and species composition of chaoborid assemblages. We expected total Chaoborus abundance to be inversely correlated with fish abundance and Chaoborus species most sensitive to fish predation to be found only in fishless lakes. We aimed to use the observed relationships to develop models to reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Below this, Chaoborus mandibles exceed 3% only once. Mandible concentrations are low with a maximum of only 6 individuals/cm , which is comparable to concentrations at some sites (Uutala 1990), but orders of magnitude less than at others (Palm et al 2012;Tolonen et al 2012). Mandibles in most samples are either Chaoborus flavicans or C. trivittatus.…”
Section: Chironomid Assemblagesmentioning
confidence: 68%
See 1 more Smart Citation
“…Below this, Chaoborus mandibles exceed 3% only once. Mandible concentrations are low with a maximum of only 6 individuals/cm , which is comparable to concentrations at some sites (Uutala 1990), but orders of magnitude less than at others (Palm et al 2012;Tolonen et al 2012). Mandibles in most samples are either Chaoborus flavicans or C. trivittatus.…”
Section: Chironomid Assemblagesmentioning
confidence: 68%
“…The sedimentary remains of Chaoborus species have been used in paleolimnological studies as a proxy for fish presence (e.g. Uutala 1990;Lamontagne and Schindler 1994;Uutala and Smol 1996;Palm et al 2012) and even fish biomass and population density (Tolonen et al 2012). The basis for this approach centers on whether Chaoborus species are capable of diurnal migration to avoid predation by fish, which is the case in C. flavicans and C. trivittatus (Uutala 1990).…”
Section: Chaoborus As a Proxy For Fish Presencementioning
confidence: 99%
“…Fossil invertebrate remains reveal information about food-web structures, predatorprey dynamics, and they are useful for investigating the influence of invertebrate competition and predation on zooplankton size structure (Alexander and Hotchkiss, 2010). Invertebrate remains have been used to document the presence or absence of fish, often for specific fish families (e.g., Cyprinidae), to identify changes in fish planktivory, and to examine keystone fish predation (Palm et al, 2011;Tolonen et al, 2012;Twining and Post, 2013;Labaj et al, 2013). The use of these fossils to address aquatic trophic-web questions often relies on contemporary limnological information about zooplankton community structure in lakes with and without fish.…”
Section: Paleolimnological Lessons Regarding Aquatic Food Websmentioning
confidence: 99%
“…The use of these fossils to address aquatic trophic-web questions often relies on contemporary limnological information about zooplankton community structure in lakes with and without fish. For example, Tolonen et al (2012) used modern and fossil phantom-midge data to derive Chaoborus-based regression models for small Swedish lakes, and to reconstruct past changes in fish biomass and density. Their study demonstrated the usefulness of certain chaoborid taxa as indicators of limnological conditions, such as basin morphometry and water transparency.…”
Section: Paleolimnological Lessons Regarding Aquatic Food Websmentioning
confidence: 99%
“…appeared and occurred in high percentages. Their coexistence with fish requires low water clarity (Wissel et al, 2003;Tolonen et al, 2012). The appearance of Chaoborus sp.…”
Section: Discussionmentioning
confidence: 99%